2001
DOI: 10.1089/088922201750290041
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Chemokine Receptor Usage in Mother-to-Child Transmission

Abstract: To investigate the role of the HIV-1 phenotype in mother-to-child HIV-1 transmission, we evaluated coreceptor usage and replication kinetics in chemokine receptor-expressing U87MG.CD4 cells of primary isolates from 32 HIV-1-infected mothers of Italian origin, none under preventive antiretroviral therapy, and from their infected infants. Five of 15 mothers of infected children and 2 of 17 mothers of uninfected children harbored viruses able to use CXCR4 as coreceptor. However, all isolates used CCR5, alone or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 73 publications
0
40
0
1
Order By: Relevance
“…Moreover, Tkachuk et al (68) found that P. falciparum infection enhances CCR5 mRNA expression on placental M of pregnant women. CCR5 is an important coreceptor required for efficient HIV-1 cell entry (69) and has been identified as the main secondary receptor implicated in HIV-1 vertical transmission (70). In addition to CCR5, it was ascertained that CCR2 (71) and CXCR4 (72) could also serve as cofactors to permit HIV-1 entry.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tkachuk et al (68) found that P. falciparum infection enhances CCR5 mRNA expression on placental M of pregnant women. CCR5 is an important coreceptor required for efficient HIV-1 cell entry (69) and has been identified as the main secondary receptor implicated in HIV-1 vertical transmission (70). In addition to CCR5, it was ascertained that CCR2 (71) and CXCR4 (72) could also serve as cofactors to permit HIV-1 entry.…”
Section: Discussionmentioning
confidence: 99%
“…Three days postinfection cells were lysed and luciferase activity was analyzed on a luminometer. CD4 þ T cells isolated from leukophereses (RosetteSep CD4 þ T-cell kit; Stemcell Technologies) were stimulated at 4Â10 6 cells=ml with 1 ml=ml anti-CD3 (eBioscience), 1 ml=ml anti-CD28 (Becton Dickinson), and 20 U=ml of interleukin-2 (IL-2, Sigma) for 3 days. For inhibition experiments with CCR5 antagonists or enfuvirtide, 1.25Â10 5 CD4 þ T cells were preincubated with drug for 30 min, infected with 25 ng virus by spinoculation (450Âg, 2 h), and incubated at 378C for 72 h before lysis and analysis.…”
Section: Virus Infection Assaysmentioning
confidence: 99%
“…1,2 CCR5 is a promising pharmacological target as most infections in new hosts are caused by HIV-1 strains that utilize CCR5 (R5-tropic), [3][4][5][6][7] R5 strains usually predominate for years after initial infection, [7][8][9] and the absence of CCR5 in patients homozygous for the D32-CCR5 polymorphism results in substantial protection against HIV-1 infection. [10][11][12] Several CCR5 antagonists have been shown to reduce virus load in HIV-infected patients including vicriviroc, aplaviroc (APL), and maraviroc.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous studies in which the R5 phenotype was predominantly transmitted from mother to child. 38,39 In contrast, one child (HN46) harbored both R5 and X4 viruses at birth with relatively high diversity, suggesting that multiple HIV-1 strain transmission occurred in utero and evolved to some extent by delivery. However, whether HIV infection was initiated with both R5 and X4 viruses or only R5 virus(es) that evolved in utero to produce X4 virus populations in this child cannot be determined because no data were available on the mother's virus and X4 and R5/X4 viruses can be transmitted from mother to child before, during, or shortly after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…8 A strong selection for viral variants using CCR5 as a coreceptor occurs during transmission, as most children are infected with R5 viruses. [9][10][11][12] Prevention of mother-to-child transmission (PMTCT) of HIV-1 is one of the key components of the worldwide response to the pandemic and is based on the prophylactic use of antiretroviral drugs (ARVs). In developed countries, MTCT of HIV-1 has been reduced to less than 2% by combination antiretroviral therapy (ART), selective caesarian delivery, and avoidance of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%